Dinamika Kelompok Usaha Budidaya Karamba Jaring Tancap (Studi Kasus di Desa Ranomerut Kecamatan Eris Kabupaten Minahasa) - Embram, Javens; Andaki, Jardie A.; Manoppo, Victoria E.N.; Tambani, Grace O.; Rantung, Steelma V.; Kotambunan, Olvie V. (AKULTURASI, 2025)
Abstract The objectives of this study are: 1) to identify the activities of fixed net cage business groups and 2) to determine the dynamics of fixed net cage business groups in Ranomerut Village, Eris District, Minahasa Regency. The method used in this study is a case study. The data collected in this study consists of primary data and secondary data. Primary data was obtained by direct interviews at the location and if there is still insufficient data, additional data will be collected to complete the analysis, by telephone directly with respondents or also through the manager of this business. Secondary data was obtained from reading materials related to the data needed, as well as citing data in Ranomerut Village and data at PT. Ranofishery Tondano Indonesia or also through readings in related journals and other literature that supports this research. The data obtained were processed, tabulated and analyzed descriptively analytically, the research method used a descriptive analytical research method. Based on the results of the research and discussion that have been explained, it can be concluded: 1) the daily activities of the KJT processing group in Ranomerut Village, Eris District, Minahassa Regency are catching fish and marketing their catch. Other activities that have become habits include if one of the members of the KJT processing group experiences a disaster such as illness, accident, or grief, then each other member will provide assistance in the form of manpower or funds. All of these activities are carried out to increase the cohesiveness and activeness of the members of the KJT processing group; and 2) the importance of group dynamics because the KJT processing group as individuals cannot live alone in the community environment and cannot work alone to meet their living needs. The dynamics of the KJT processing group in Ranomerut Village, Eris District, Minahasa Regency show that the existence of a fishing group brings a good process of change to the lives of fish processors. The group helps KJT processors in solving problems, increasing cooperation (mutual cooperation), work becomes easier to complete, and income increases. Keywords: dynamics, business groups, fixed net cages Abstrak Tujuan dari penelitian ini, yaitu: 1) mengidentifikasi aktivitas kelompok usaha karamba jaring tancap dan 2) menentukan dinamika kelompok usaha karamba jaring tancap di Desa Ranomerut Kecamatan Eris Kabupaten Minahasa. Metode yang digunakan dalam penelitian ini adalah studi kasus. Data yang dikumpulkan pada penelitian ini terdiri dari data primer dan data sekunder. Data primer diperoleh dengan wawancara langsung di lokasi dan jika masih kurang data maka akan dilakukan tambahan data untuk kelengkapan analisis, melalui telepon langsung dengan responden atau juga melalui pengelola usaha ini. Data sekunder diperoleh dari bahan bacaan yang berkaitan dengan data yang dibutuhkan, serta mengutip data yang ada di Desa Ranomerut dan data yang ada di PT. Ranofishery Tondano Indonesia atau juga melalui bacaan di Jurnal-Jurnal yang terkait serta literatur-literatur yang lain yang menunjang penelitian ini. Data yang diperoleh diolah, ditabulasi dan dianalisis secara deskriptif analitik, metode penelitiannya menggunakan metode penelitian deskriptif analitik. Berdasarkan hasil penelitian dan pembahasan yang telah dijelaskan, maka dapat disimpulkan: 1) aktivitas kelompok pengolah KJT di Desa Ranomerut Kecamatan Eris Kabupaten Minahasasehari-harinya melakukan penangkapan ikan dan memasarkan hasil tangkapannya. Aktivitas lain yang sudah menjadi kebiasaan antara lain jika ada salah satu anggota kelompok pengolah KJT yang mengalami peristiwa bencana seperti sakit, kecelakaan, atau kedukaan, maka setiap anggota yang lain akan memberikan bantuan baik berupa tenaga atau dana. Semua aktivitas tersebut dilakukan untuk meningkatkan kekompakkan dan keaktifan anggota kelompok pengolah KJT; dan 2) pentingnya dinamika kelompok dikarenakan kelompok pengolah KJT sebagai individu tidak dapat hidup sendiri dalam lingkungan masyarakat dan tidak dapat bekerja sendiri untuk memenuhi kebutuhan hidup. Dinamika kelompok pengolah KJT di Desa Ranomerut Kecamatan Eris Kabupaten Minahasa menunjukkan bahwa keberadaan kelompok nelayan membawa proses perubahan yang baik bagi kehidupan pengolah ikan. Kelompok membantu pengolah KJT dalam memecahkan masalah, meningkatkan kerja sama (gotong royong), pekerjaan menjadi lebih mudah diselesaikan, dan pendapatan semakin meningkat. Kata kunci: dinamika, kelompok usaha, karamba jaring tancap